Treatment of pseudoepitheliomatous, keratotic, and micaceous balanitis with topical photodynamic therapy. (30th September 2014) - Zhu, Hui; Jiang, Yong; Watts, Matthew; Kong, Fanrong
Abstract Background Pseudoepitheliomatous, keratotic, and micaceous balanitis (PKMB) is an extremely rare condition occurring over the glans in older men who undergo circumcision late in life. Its exact etiology is unknown. Objectives We report a patient with PKMB that involved the meatus and led to urinary obstruction. Methods A 57‐year‐old, circumcised man presented with partial urinary obstruction caused by a thick, nail‐like covering on the skin of his glans penis. Based on histology, PKMB was diagnosed. There was no cytological atypia. The patient was treated successfully with topical 5‐aminolevulinic acid (ALA) photodynamic therapy (PDT). Results There was no recurrence after 18 months of follow‐up. Treatment with ALA–PDT seems to be effective and well tolerated in PKMB. Conclusions This case indicates that ALA–PDT may be an effective treatment option for plaque‐stage PKMB and thus warrants further investigation.